Hadith #137 - Sahih Muslim - Zaid bin Khalid al-Juhani (Sahih Muslim)
The Messenger of Allah (may peace and blessings be upon him) led the morning prayer at Hudaybiya. There were some marks of the rainfall during the night. At the conclusion of prayer he turned towards people and observed: Do you know what your Lord has said? They replied: Allah and His Messenger know best. Upon this he (the Holy Prophet) remarked: He (Allah) said: Some of My bondsmen entered the morning as My believers and some as unbelievers. He who said: We have had a rainfall due to the Blessi
Grade: Sahih

Hadith #686 - Sahih Muslim - Zaid bin Khalid al-Juhani (Sahih Muslim)
What is your opinion about the man who has sexual intercourse with his wife, but does not experience orgasm? Uthman said: He should perform ablution as he does for prayer, and wash his organ. ‘Uthmin also said: I have heard it from the Messenger of Allah (ﷺ).
Grade: Sahih

Hadith #1696 - Sahih Muslim - Zaid bin Khalid al-Juhani (Sahih Muslim)
I would definitely watch at night the prayer observed by the Messenger of Allah (ﷺ). He prayed two short rak’ahs, then two long, long, long rak’ahs, then he prayed two rak’ahs which were shorter than the two preceding rak’ahs, then he prayed two rak’ahs which were shorter than the two preceding, then he prayed two rak’ahs which were shorter than the two preceding, then observed a single one (Witr), making a total of thirteen rak’ahs
Grade: Sahih

Hadith #4364 - Sahih Muslim - Zaid bin Khalid al-Juhani (Sahih Muslim)
Should I not tell you of the best witnesses? He is the one who produces his evidence before he is asked for it.
Grade: Sahih

Hadith #4368 - Sahih Muslim - Zaid bin Khalid al-Juhani (Sahih Muslim)
A man came to Allah’s Apostle (ﷺ) and asked him about picking up of stray articles. He said: Recognise (well) its bag and the strap (by which it is tied) then make announcement of that for a year. If its owner comes (within this time return that to him), otherwise it is yours. He (again) said: (What about) the lost goat? Thereupon he (the Holy Prophet) said: It is yours or for your brother, or for the wolf. He said: (What about) the lost camel? Thereupon he said: You have nothing to do with
Grade: Sahih

Hadith #4369 - Sahih Muslim - Zaid bin Khalid al-Juhani (Sahih Muslim)
Make announcement about it for a year, and recognise well the strap and the bag (containing that) ; then spend that; and if its owner comes, make him the payment of that. He (the inquirer) said: Messenger of Allah, what about the lost goat? he said: Take it, for that is yours or for your brother, or for the wolf. He (again) said: (What about) the lost camel? The Messenger of Allah (ﷺ) was enraged until his cheeks became red (or his face became red) and then said: You have nothing to do about t
Grade: Sahih

Hadith #4371 - Sahih Muslim - Zaid bin Khalid al-Juhani (Sahih Muslim)
His face became red, his forehead too, and he felt annoyed; and made an addition after the words: He should make announcement of that for a year, and if its owner does not turn up, then it is a trust with you.
Grade: Sahih

Hadith #4372 - Sahih Muslim - Zaid bin Khalid al-Juhani (Sahih Muslim)
Recognise well the strap and the bag (containing) that and then make an announcement regarding that for one year, but if none recognises it, then spend that and it would be a trust with you; and if someone comes one day to make demand of that, then pay that to him. He (the inquirer) asked about the lost camel, whereupon he said: You have nothing to do with that. Leave that alone, for it has feet and also a leather bag, it drinks water, and eats (the leaves) of the trees. He asked him about sheep
Grade: Sahih

Hadith #4373 - Sahih Muslim - Zaid bin Khalid al-Juhani (Sahih Muslim)
A person asked Allah’s Apostle (ﷺ) about a lost camel; Rabi’a made this addition: He (the Holy Prophet) was so much annoyed that his cheeks became red.” The rest of the hadith is the same. He (the narrator) made this addition:” If its (that of the article) owner comes and he recognises the bag (which contained it) and its number, and the strap. then give that to them, but if not, then it is for you.”
Grade: Sahih

Hadith #4374 - Sahih Muslim - Zaid bin Khalid al-Juhani (Sahih Muslim)
Make announcement of that for one year, but if it is not recognised (by the owner), then recognise its big and strap, then eat it; and if its owner comes, then give that to him. This hadith has been narrated on the authority of Al-Dahhak b. Uthman with the same chain of transmitters but with a slight variation of words.
Grade: Sahih

Hadith #4379 - Sahih Muslim - Zaid bin Khalid al-Juhani (Sahih Muslim)
He who found a stray article is himself led astray if he does not advertise it.
Grade: Sahih

Hadith #4767 - Sahih Muslim - Zaid bin Khalid al-Juhani (Sahih Muslim)
Anybody who equips a warrior (going to fight) in the way of Allah (is like one who actually) fights. And anybody who looks well after his family in his absence (is also like one who actually) fights.
Grade: Sahih